Food waste perceptions: vice versus virtue foods. Issue 3 (4th April 2022) - Seo, Joon Yong; Yoon, Sukki
Abstract : Purpose: Food waste has strong ecological, economical and social implications. Focusing on waste perceptions and behavior according to food types, this paper aims to propose that vice or virtue food categories determine cognitive and behavioral reactions to food waste. The authors examine the psychological mechanism underlying the differential waste perceptions and behavior. Design/methodology/approach: The authors conduct five studies, including a field study, to provide converging evidence that supports this theorization. Findings: This study demonstrates that consumers feel that trashing vice food is more wasteful than trashing virtue food. They are less willing to waste vice food and more comfortable with wasting virtue food. Consequently, they waste more virtue than vice foods. The authors demonstrate that counterfactual thinking explains the food type effect on waste. Research limitations/implications: This paper provides a conceptual framework for understanding and explaining food waste perceptions and behavior across vice and virtue food categories. This paper identifies counterfactual thinking as underpinning the psychology of waste perceptions and behaviors. The findings extend the growing research on subconscious and unintentional food waste, the food consumption literature and the psychology of waste literature. Practical implications: The differential waste perceptions and behavior provide several implications for waste interventions and consumer education. By expanding theories of consumer food waste, this paper provides material for educational campaigns aimed at reducing waste and improving healthful eating. Social implications: Consumers can benefit from understanding their tendency to avoid wasting vice foods but will waste virtue foods with little compunction. Waste aversion may be a reason people consume vice foods beyond satiation. Consumers may overconsume vice foods because they are so acutely averse to wasting them, with detrimental consequences for health and welfare. Originality/value: To reduce consumer food waste, one must gain deeper insights into factors shaping consumer food waste perceptions and behavior. Food waste studies have been increasing but have overlooked the power of consumer perceptions in driving food waste consequences. To the best of the authors' knowledge, no prior study has examined how food type affects waste perceptions and behavior. This research fills this gap.